Corporate Human Rights Due Diligence in Transnational Business: Towards a Binding Normative Framework in International Private Law - Cindya Cindya; Dedy Ardian Prasetyo; Supaphorn Akkapin (CV. Era Digital Nusantara, 2025)
The global expansion of transnational corporations has intensified concerns over human rights (HR) violations, including forced labor, environmental harm, and the displacement of local communities. Existing international instruments—such as the UN Guiding Principles on Business and Human Rights (UNGPs) and OECD Guidelines—remain non-binding and lack effective enforcement. While regional initiatives like the European Union’s Corporate Sustainability Due Diligence Directive (CSDDD) signal a transition toward binding obligations, their territorial scope limits broader applicability. This gap underscores the pressing need for normative frameworks that supersede voluntary standards. This study adopts a normative juridical methodology, analyzing international instruments, landmark cases (Kiobel v. Royal Dutch Petroleum and Chevron v. Ecuador), and comparative regulatory approaches. The findings demonstrate that private international law offers untapped potential to embed HR due diligence (HRDD) obligations within transnational business practices. Contractual mechanisms, choice of law clauses, and international arbitration can transform HRDD into binding legal commitments, complementing public international law while addressing jurisdictional and enforcement barriers. The novelty of this research lies in reframing private international law as a substantive tool for human rights enforcement. It advances the paradigm of “privatization of human rights accountability,” expanding the discourse on corporate accountability beyond the limits of public law. Practically, the study contributes actionable models for regulators and corporations to integrate HRDD into global supply chains, thereby strengthening both human rights protection and sustainable corporate governance